Clinical application of comprehensive genomic profiling panel to thoracic malignancies: A single‐center retrospective study. Issue 21 (13th September 2022) - Kunimasa, Kei; Sugimoto, Naotoshi; Kawamura, Takahisa; Yamasaki, Tomoyuki; Honma, Keiichiro; Nagata, Shigenori; Kukita, Yoji; Fujisawa, Fumie; Inoue, Tazuko; Yamaguchi, Yuko; Kitasaka, Mitsuko; Wakamatsu, Toru; et al.
Abstract: Background: The usefulness of comprehensive genomic profiling (CGP) panels for thoracic malignancies after completion of the standard treatment is unclear. Methods: The results of CGP panels for malignant thoracic diseases performed at our hospital between December 2019 and June 2022 were collected. We examined whether CGP panel results led to new treatment, correlated with the effectiveness of immune checkpoint inhibitors (ICIs), or revealed secondary findings related to hereditary tumors. Results: A total of 60 patients were enrolled, of which 52 (86.6%) had lung cancer. In six (10%) patients, the panel results led to treatment with insurance‐listed molecular‐targeted agents; four patients had EGFR mutations not detected by the real‐time polymerase chain reaction assay and two had MET ex.14 skipping mutations. In small‐cell lung cancer, the tumor mutation burden was high in 4/6 (66.7%) patients and pembrolizumab was available. Another MET ex.14 skipping mutation was detected in two cases with EGFR‐tyrosine kinase inhibitor resistance. ICI efficacy was ≤1 year in patients with STK‐11, KEAP1, and NEF2L2 mutations. A BRCA2 mutation with a high probability of germline mutation was detected in one patient. A thymic carcinoma with no detectable oncogenic mutation responded to second‐line treatment with Tegafur‐Gimeracil‐Oteracil Potassium (TS‐1) for ≥9 years. Conclusions: CGP panels are useful in thoracic malignancies, especially lung cancer, because they can detect overlooked driver mutations and genetic alterations. We believe that the significance of conducting a CGP panel prior to treatment may also exist, as it may lead to the prediction of ICI treatment efficacy. Abstract : The usefulness of comprehensive genomic profiling (CGP) panels for thoracic malignancies is unclear. A total of 60 patients were enrolled and in six (10%) patients the panel results led to treatment with insurance‐listed molecular‐targeted agents. Immune checkpoint inhibitor efficacy was poor in patients with STK‐11, KEAP1, and NEF2L2 mutations. CGP panels are useful because they can detect overlooked driver mutations and genetic alterations, and lead to the prediction of ICI treatment efficacy.